MXene aerogel for efficient photothermally driven membrane distillation with dual-mode antimicrobial capability. Issue 39 (30th September 2021) - Cao, Sisi; Wu, Xuanhao; Zhu, Yaguang; Gupta, Prashant; Martinez, Adrian; Zhang, Yunzhu; Ghim, Deoukchen; Wang, Yixuan; Liu, Lin; Jun, Young-Shin; Singamaneni, Srikanth
Abstract : A MXene-based composite aerogel enabling highly efficient photothermally driven membrane distillation with dual-mode anti-biofouling properties make it highly appealing for solar-driven desalination. Abstract : Solar-driven desalination, which involves the conversion of solar energy to heat for freshwater generation, has been recognized as an attractive and sustainable desalination technology to alleviate freshwater shortage. In particular, photothermally driven membrane distillation (PMD) is a highly promising solar-driven desalination technology, especially in remote regions and disaster-struck communities, where no power infrastructure or waste heat from industrial plants is available. MXene, more specifically Ti3 C2 T x, with excellent photothermal properties, easy processability, and electrical conductivity offers a great opportunity for realizing highly efficient, stable and multifunctional PMD membranes. Herein, we realize a MXene composite aerogel comprised of hydroxyapatite nanowires and poly(vinyl alcohol) with high thermal efficiency (61%) and water flux (0.72 kg m −2 h −1 ) under 0.8 sun irradiation (0.8 kW m −2 ), representing the first validation of highly efficient MXene-based PMD systems in treating ambient saline water. Owing to the strong interfacial interaction ( i.e., hydrogen bonding) between the building blocks, the MXene composite aerogel with high porosity (up to 91%) exhibited excellent mechanical stability. This highly interconnected porous network offers low resistance to vapor transport and low thermal conductivity, which minimizes conductive heat transfer across the aerogel, thus maximizing the thermal efficiency. Furthermore, the outstanding bactericidal activity induced by solar irradiation or electric potential makes the MXene composite aerogel a highly attractive candidate for PMD in the real world.